Facing multiple challenges: the future of flooding in Can Tho city - Huong, Huynh Thi Lan; Assela, Pathirana; Thuc, Tran (VNU Journal of Science: Earth and Environmental Sciences, 2012)
Abstract. In this paper, we present the case study of Can Tho city (the biggest city in Mekong River Delta, Vietnam), faced with multiple future challenges, namely, (i) climate change driven sea-level rise and tidal effect, (ii) increased river runoff due to climate change, (iii) increased urban runoff driven by imperviousness and (iv) enhancement of extreme rainfall due to urban growth driven micro-climatic change (urban heat islands). A set of models were used to project the future impact of the combination of these influences. Urban growth of the city was projected using the landuse simulation model (Dinamica-EGO) to predict the future landuse up to 2100. The dynamic limited-area atmospheric model (WRF) coupled with a detailed land-surface model with vegetation parameterization (Noah LSM) were used to estimate the anticipated changes in extreme rainfall patterns due to urban heat island effects. Finally a 1-D/2-D coupled urban drainage/flooding models (SWMM-Brezo) were used to simulate storm-sewer surcharge and surface inundation to establish the increase in the flood risk resulting from the changes. The results show that, if the city is developed as prediction, the maximum of inundation depth and area in Can Tho city may increase about 20%. The impacts of climate change on inundation are more serious than that of urbanization. Key words: urbanization, urban heat island, flooding.